Diagnostic problems in acute pancreatitis: relationship between amylasuria values and study of peritoneal exudate - Perdomo, Roberto (Cirugía del Uruguay, 2020)
Four cases of acute- pancreatitis which present troubles in order to perform a diagnosis are exposed. The real positive value of urinary amylase dosages produce errors when their marks are taken into consideration to state or refuse the diagnosis of acute pancreatitis. W e have found examples of false-positive dosage in bowel strangulation; false. negative dosage in an acute necrotizing haemorragic pancreatitis, and a questionable one in a developed acute pancreatitis. It is difficult to perform a diagnosis in acute pancreatitis and biliar-peritonitis connected, specially in bilio pancreatic and pancreatic-biliar peritonitis, as they were called by Tejerina Fotheringham. At last, we can emphasize that the study of pancreatitis is harmless, when it is positive, in order to perform the difinitive diagnosis. Therefore, the author analyses: 1) the physical characteristics of peritoneal fluid; 2) the hígher persistent nucleous .f amylase in this fluid than in seru and urine, and 3) other chemical an citobacteriological studies that help to p form the diagnosis of acute pancreatitis.